Implementasi Metode Time Out Dalam Mengatasi Temper Tantrum pada Anak Usia Dini Kelompok B di RA Salafiyah Desa Cibenda Parigi Pangandaran - Ujang Sutaryat; Cucu Nurhasanah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
Temper tantrums are destructive behavior, in the form of outbursts which can be physical in nature such as hitting, pushing, slamming an object or in a verbal form, such as screaming, crying, screaming or whining. One method that can be used to deal with temper tantrums is the methodtime out. Methodtime out defined as withdrawing opportunities to gain positive reinforcement or loss of positive reinforcement for a given time, in order to reduce the probability of future behavior. The purpose of this study is regarding the role of educators in implementing the handling of children with temper tantrums through the temper tantrum method. This research method is descriptive qualitative. Data was collected through observation, documentation, interviews and document analysis. Data is analyzed using data reduction, displaying data and drawing conclusions. The results of this study indicate that the process of handling children who experience tantrums uses a momentary allowance technique (Time Out) can make children calmer, emotions more controllable and able to accept stimulus handling given by other people to children.